2018
DOI: 10.1016/j.jaim.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Ayurveda and the science of aging

Abstract: Since time immemorial, humanity has been concerned with developing and preserving youthful vigor, and extending longevity by stopping or delaying the aging process. By 2030, one in five of the world population will be over 65 years old. Longevity and old age are accompanied with a variety of health challenges and population studies indicate that the elderly will use between three to five times more healthcare services compared to the younger population. Modern medicine has made a great deal of progress in unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 99 publications
0
15
0
3
Order By: Relevance
“…The abovementioned study design is similar to our therapeutic program for people with SCI and MCI, where Bm is administered in combination with other nutraceuticals and cogniceuticals [ 15 , 111 ].…”
Section: Introductionmentioning
confidence: 99%
“…The abovementioned study design is similar to our therapeutic program for people with SCI and MCI, where Bm is administered in combination with other nutraceuticals and cogniceuticals [ 15 , 111 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aging is found associated with several disease conditions and characterized by a gradual functional decline posing a significant risk for neurodegenerative diseases, cancers, cardiovascular diseases, and diabetes [18]. Ayurveda considered aging as an important health context since ancient times [19]. It is referred to as "Jara" (aging or declining phase) in classical Ayurveda.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies were reported from different healthcare disciplines regarding prevention of COVID-19 [30][31][32][33][34].…”
Section: Recommendation For Ayush Initiativesmentioning
confidence: 99%